Stem borers of cereal crops in Africa and their management - Togola, A.; Boukar, O.; Tamo, Manuele; Chamarthi, S. (IntechOpen, 2020)
The economic importance of the stem borer in Africa results in their severe damage that affect directly cereal yield factors such as the density of fertile tillers and the number of effective panicles. The objective of this paper is to describe and discuss the management options of the main prevalent stem borer of cereal crops in Africa. Host plant resistance, cultural practices, biological control and reasoning chemical control are among the most encouraging options. Integrated pest management combining several compatible methods was highlighted as the most sustainable control option. This paper will served as support for the current research on cereal crops but also as relevant prospect document for entomologists and breeders from across the world.